O uso sustentável de recursos comuns em um jogo digital - Oliveira, Marlon Alexandre de (2022)
The PhD dissertation contains three chapters in paper format The first chapter presents a theoretical article about sustainability, the use of common access resources and analytical-behavioral studies related to environmental sustainability. It aims, from a description of the concepts of sustainability and common access resources, to point out how research on promoting the use of collective goods in the experimental analysis of behavior is carried out and to discuss possible dependent variables to be investigated through digital games. The second chapter is in the format of a scientific paper and is written in English. Its content involves an experiment carried out with six children individually exposed to a digital game named Fishing Cards, in which in the first stage they captured fish by choosing cards with pictures related to fishing technologies (fishing rod, fishing boat and radar), which had different capacities to the extraction of common resources and should be used to fish in successive rounds, until completion. However, at a later stage, resources were limited and shared with virtual players. Faced with this challenge, the victorious participant played in a way that promoted the sustainability of resources and remained “alive” throughout the rounds. The experiment in the second chapter identified that the players present response patterns of sustainable use of renewable natural resources. Changes were observed in fishing speed and choices of cards with lower resource extraction capabilities to provide maintenance. Its main contribution was to demonstrate, in a digital game context, children can adopt different strategies to overcome the extinction of the commons by increasing the interval between their responses and changing the amount of extraction. Finally, the third chapter presents another scientific paper, however, unlike the previous one, it is in Portuguese. In the experiment of the third chapter, an adapted version of the digital game was used to allow remote collection in which adults and adolescents had to capture fish identically to the previous experiment, dealing with the same challenge. The results found were the absence of differences between the management of the resource by the groups of adults and adolescents, again the decrease in the pace of fishing speed and the allocation of the use of cards was an effective strategy to win the game. In general, the findings of the experiments revealed that the game Fishing Cards advances in the understanding of the conflict between the individual and immediate consequences acting in a scenario of Tragedy of the Commons, showing that individual behavior can be modeled in the long term establishes consequences of reinforcement positive for the collective good (i.e. conservation of commonly available renewable natural resources).